Why movement disorders should be a formally acknowledged subspecialty of neurology editorial - Dirk Dressler; Ivan Milanov (Българска неврология, 2019)
DISCLOSURES DD received honoraria for services provided to Allergan, Ipsen, Merz, Lanzhou Institute of Biological Products, MedyTox, Revance, Desitin, Syntaxin, Abbvie, Medtronic, St Jude, Boston Scientific, Almirall, Bayer, Sun, Teva, UCB, IAB-Interdisciplinary Working Group for Movement Disorders. He is shareholder of Allergan and holds patents on botulinum toxin and botulinum toxin therapy.